2008
DOI: 10.1111/j.1442-200x.2007.02512.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior choroid plexus cysts: Distinction from germinolysis by high‐resolution sonography

Abstract: ACPC are not rare and are identified by their location, form, and movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
1
1
1
Order By: Relevance
“…One explanation for the high rate of SEP and CPC in our study might also be that we performed high-resolution cUS; van Baalen and Versmold35 found, using high-resolution cUS, that 5% of German infants had CPC, higher than found in other studies.…”
Section: Discussioncontrasting
confidence: 56%
“…One explanation for the high rate of SEP and CPC in our study might also be that we performed high-resolution cUS; van Baalen and Versmold35 found, using high-resolution cUS, that 5% of German infants had CPC, higher than found in other studies.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been postulated in the literature that high-resolution sonography and the position of the cystic lesion would help distinguish between haemorrhagic and non-haemorrhagic germinolysis 42 43. Furthermore sonographic criteria have been published to distinguish between subependymal pseudocysts and choroid plexus cysts 44. Based on the above mentioned facts and our own experience we feel that this is not necessary.…”
Section: Discussionmentioning
confidence: 85%
“…En sık saptanan anormal bulgular; BOS mesafelerinde genişleme (%4,4), hidrosefali (%3,8), subaraknoid mesafede genişleme (%2,7), en az saptanan anormal bulgular; ventrikül kisti (%0,5), subdural mesafede artma (%0,5), germinal matriks kanaması (%0,5), kalsifikasyon (%0,5) ve mega sisterna magna (%0,5) idi. Çeşitli çalışmalarda subependimal kistler ve koroid pleksus kistleri yenidoğan döneminde kraniyal ultrason taramalarında yaygın olarak saptanmıştır ve yenidoğan popülasyonunun %1-%5'inde bildirilmiştir (17,18). Bizim çalışmada ise koroid pleksus kistleri %1,6 oranında saptanmıştır.…”
Section: Discussionunclassified